Inverse design of perimeter-controlled InAs-assisted metasurface for two-dimensional dynamic beam steering - Sabri Raana; Mosallaei Hossein (Nanophotonics)
The current commercially viable light detection and ranging systems demand continuous, full-scene, and dynamic two-dimensional point scanning, while featuring large aperture size to ensure long distance operation. However, the biasing architecture of large-area arrays with numerous individually controlled tunable elements is substantially complicated. Herein, inverse design of a perimeter-controlled active metasurface for two-dimensional dynamic beam steering at mid-infrared regime is theoretically presented. The perimeter-control approach simplifies biasing architecture by allowing column-row addressing of the elements. The metasurface consists of a periodic array of plasmonic patch nanoantennas in a metal-insulator-metal configuration, wherein two active layers of indium arsenide are incorporated into its building block. The metasurface profile facilitates wide phase modulation of ≈355°$≈ 355^{°} $ on the reflected light at the individual element level through applying independent voltages to its respective columns and rows. The multi-objective genetic algorithm (GA) for optimizing user-defined metrics toward shaping desired far-zone radiation pattern is implemented. It is demonstrated that multi-objective GA yields better results for directivity and spatial resolution of perimeter-controlled metasurface by identifying the design tradeoffs inherent to the system, compared to the single-objective optimizer. A high directivity and continuous beam scanning with full and wide field-of-view along the azimuth and elevation angles are respectively maintained.